Influence of crack growths on the performances of cantilever based MEMS devices: Design and simulations - Jan, M.T. (IEEE Computer Society, 2014)
There is a great need to design experimental setup to deal with the fundamental material issues in MEMS. Cantilever being the active part of MEMS is modeled using COMSOL Multiphysics. The model is simulated for small cracks ranging from Nano to Micro-meter. The cracks are produced at the anchor of MEMS device subjected to variations in Eigen frequencies, Stress levels and Tip displacements of cantilever beam and is measured in association with crack growths. These factors are simulated in order to predict the ultimate lifetime in the form of total number of cycles to failure in association with variations in applied stress levels and with the help of Statistical distribution and Paris's law. The Paris's law is utilized by integrating it between the upper and lower limits (crack sizes) that results in predicting the useful lifetime of the cantilever based MEMS device. The simulated results show that at resonance frequency the probability of crack growth is less due to its stress-less and free vibration. The tip displacement of the cantilever also contributes in deterioration in resonance frequency. Moreover, periodically increase in applied stresses result in rapid crack growth. Â© 2014 IEEE.